2009
DOI: 10.1186/1748-7161-4-24
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of adolescent idiopathic scoliosis in girls - a double neuro-osseous theory involving disharmony between two nervous systems, somatic and autonomic expressed in the spine and trunk: possible dependency on sympathetic nervous system and hormones with implications for medical therapy

Abstract: Anthropometric data from three groups of adolescent girls - preoperative adolescent idiopathic scoliosis (AIS), screened for scoliosis and normals were analysed by comparing skeletal data between higher and lower body mass index subsets. Unexpected findings for each of skeletal maturation, asymmetries and overgrowth are not explained by prevailing theories of AIS pathogenesis. A speculative pathogenetic theory for girls is formulated after surveying evidence including: (1) the thoracospinal concept for right t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 302 publications
(544 reference statements)
6
100
0
2
Order By: Relevance
“…Several morphological studies have reported that individuals with AIS have imbalanced and faster longitudinal growth of the vertebral bodies, as well as extraspinal skeletal length asymmetries [10][11][12]. A recent study reported that GPR126-null mice have limb posture abnormalities and growth failure [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several morphological studies have reported that individuals with AIS have imbalanced and faster longitudinal growth of the vertebral bodies, as well as extraspinal skeletal length asymmetries [10][11][12]. A recent study reported that GPR126-null mice have limb posture abnormalities and growth failure [13].…”
Section: Introductionmentioning
confidence: 99%
“…6 According to many authors, gravity plays a role in the development and progression of scoliosis. 7 Even in ancient times, Hippocrates attempted hanging patients with scoliosis to counteract the negative effect of spinal load or to place the spine in traction using specific tools, the Hippocratic board and the Hippocratic ladder. 8 Despite these theories, however, as far as we know no data have been published to support the efficacy of swimming as a specific scoliosis treatment.…”
mentioning
confidence: 99%
“…We have recently defined idiopathic scoliosis as a www.intechopen.com multi-factorial three-dimensional deformity of the spine and the trunk, which appears and can progress during any of the rapid periods of growth in apparently healthy children. The aetiology is unknown but some models explain how idiopathic scoliosis develops and progresses (Burwell, 2009). The basic scoliosis deformity is classically described as a lateral deviation of the spine associated with axial rotation, however, it can be better defined as a combination of torsional regions separated by junctional zones, each region formed by a variable number of vertebrae in extension (or lordosis) deviated and rotated to the same side (Dubousset 1992).…”
Section: Principles Of the Bspts Methodsmentioning
confidence: 99%